2015
DOI: 10.1093/femsec/fiv105
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of XoxF methanol dehydrogenases reveals new methylotrophic bacteria in pelagic marine and freshwater ecosystems

Abstract: The diversity and distribution of methylotrophic bacteria have been investigated in the oceans and lakes using the methanol dehydrogenase mxaF gene as a functional marker. However, pelagic marine (OM43) and freshwater (LD28 and PRD01a001B) methylotrophs within the Betaproteobacteria lack mxaF, instead possessing a related xoxF4-encoded methanol dehydrogenase. Here, we developed and employed xoxF4 as a complementary functional gene marker to mxaF for studying methylotrophs in aquatic environment. Using xoxF4, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…Also present are genes for the lanthanide-dependent (xoxF) methanol dehydrogenase involved in methanol oxidation to formaldehyde, NAD(P)-dependent methylene-H 4 MPT dehydrogenase (mtd) involved in formaldehyde oxidation to formate, and formate dehydrogenase (fdh) for formate oxidation to CO 2 . The presence of XoxF type methanol dehydrogenases, but absence of the calcium-dependent MxaF type, has also been reported for pelagic non-methanotrophic methylotrophs with relatively small genomes (Giovannoni et al, 2008) and is consistent with recent studies suggesting the prevalence of XoxF compared to MxaF in natural systems (Keltjens et al, 2014;Ramachandran and Walsh, 2015).…”
Section: Recovery Of the Genome Of An Opu3-like Methanotrophic Denitrsupporting
confidence: 89%
“…Also present are genes for the lanthanide-dependent (xoxF) methanol dehydrogenase involved in methanol oxidation to formaldehyde, NAD(P)-dependent methylene-H 4 MPT dehydrogenase (mtd) involved in formaldehyde oxidation to formate, and formate dehydrogenase (fdh) for formate oxidation to CO 2 . The presence of XoxF type methanol dehydrogenases, but absence of the calcium-dependent MxaF type, has also been reported for pelagic non-methanotrophic methylotrophs with relatively small genomes (Giovannoni et al, 2008) and is consistent with recent studies suggesting the prevalence of XoxF compared to MxaF in natural systems (Keltjens et al, 2014;Ramachandran and Walsh, 2015).…”
Section: Recovery Of the Genome Of An Opu3-like Methanotrophic Denitrsupporting
confidence: 89%
“…Interestingly, all methanotrophs and methylotrophs of the Methylococcaceae, Methylophilaceae and other Alphaproteobacteria detected in our incubations employed lanthanide dependent, XoxF-type methanol dehydrogenases instead of the calcium-dependent methanol dehydrogenase MxaFI. The high diversity of xoxF gene sequences in marine habitats, especially xoxF4 and xoxF5, as well as their prevalence over mxaF gene sequences, has previously been described (Ramachandran and Walsh, 2015;Taubert et al, 2015). The lanthanides required for these enzymes, belonging to the rare earth elements, are typically present in sufficient concentrations in coastal environments from sediments or coastal run-off, despite their low solubility (Elderfield et al, 1990;Keltjens et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A XoxF survey in coastal marine environments revealed the existence of the gene in a high number of unknown bacterial species (Taubert et al ., ). Comparative metagenomics also showed that uncultured methylotrophs in the ocean and freshwaters of North America (Ramachandran and Walsh, ) and uncultured lineages of two novel Type I methanotrophs from North Sea sediments (Vekeman et al ., ) possessed only XoxF‐MDH but not MxaFI‐MDH. A quantity of culturable facultative methylotrophic bacteria from the cactus Neobuxbaumia macrocephala showed positive hybridization with a xoxF probe, but not with a mxaF probe, while all these isolates showed methylotrophic growth in the presence of Ce 3+ or Ca 2+ (Del Rocío Bustillos‐Cristales et al ., ).…”
Section: Introductionmentioning
confidence: 99%